Mexico 2017: incumbent disadvantage ahead of 2018 - Benton, Allyson Lucinda; Robles, Edwin Atilano (Revista de Ciencia Política, 2018)
Weak economic performance, high inflation, and a devalued peso drew criticism of the incumbent Institutional Revolutionary Party’s (PRI) economic and fiscal policy choices, and kept President Enrique Peña Nieto’s approval ratings low. The incumbent PRI thus entered the 2018 electoral season in a weak position, with reduced chances of defeating its main opposition candidate, Andrés Manuel López Obrador, of the National Regeneration Movement (MORENA).